Composition and toxicity of total water-soluble flavonoids from Lithocarpus litseifolius (Hance) Chun (sweet tea) - Junfei Xu; Yingqi Zhao; Jing Wen; Ye Lin; Yangtao Li; Yijun He; Xianjin Wu; Juzuo Zhang (Food and Agricultural Immunology)
The material basis and toxicity of Lithocarpus litseifolius (Hance) Chun (sweet tea), which has many health benefits, are not fully understood. In this study, total water-soluble flavonoids were extracted from sweet tea using optimised methods based on RSM. Its composition and toxicity were investigated by LC–MS and mouse models in vivo. The results showed that the optimum extraction conditions were a liquid/solid ratio of 32.98:1 ml/g, a temperature of 60.69°C, a microwave power of 633.70 W, and a microwave time of 164.08 secs. Among the 33 main components in the extract, five flavonoids constituted more than 73.80% of the total compound content. Total flavonoids were safe after oral administration and alleviated reproductive disorders but were highly toxic after intraperitoneal injection in mice. In summary, under the optimum extraction conditions, the total water-soluble flavonoids were safe after oral administration, but the complex compounds hindered their direct injection.Abbreviations: LLHC: Lithocarpus litseifolius (Hance) Chun; SFD: single-factor design; RSM: response surface methodology; CCD: central composite design; ES: extracted solution; CS concentrated solution; LP: lyophilised powder; LC–MS: liquid chromatography–mass spectrometry; NC: negative control; PH: procaine hydrochloride; CP: cyclophosphamide group.